HUKUM EKONOMI SYARIAH ATAS BUNGA BANK - Latifah, Eny; Abdullah, Rudi (JIDE : Journal Of International Development Economics, 2022)
This research, which has the aim of knowing the sharia economic law on bank interest, uses a qualitative method with the type of literature study. Where to see Banking has the impression of a Financial Institution that runs usury with the application of interest in managerial, especially existing products. Sharia Economic Law in terms of Wasathiyah and Harakah Values found 3 views on the law of interest, namely first, Pragmatic: interest is an additional profit that can be taken from the banking business process, interest is obtained from the net profit of the bank. Second, Realist-modernist: interest is taking advantage of the benefits of the people that are measurable and do not oppress anyone Third, Fundamental: bank interest in both conventional and Islamic banking should be avoided